A self-compacting high-performance concrete cable cover
By using a defoaming water reducer with hyperbranched structure in self-fixed concrete, the problem of large amount of water required for gelling materials and the introduction of bubbles into polycarboxylic acid water reducer is solved, the flowability and resistance of concrete are improved, and high Preparation of performance cable cover plates.
Patent Information
- Application Number
- CN202410953428.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-07-16
AI Technical Summary
Too much gelling material components of self-finished concrete lead to a large amount of water demand, which is prone to self-shrinkage and drying shrinkage, increasing the risk of cracking. At the same time, the introduction of bubbles into polycarboxylic acid water reducing agent affects the strength and appearance of concrete. The existing defoaming agents in concrete Dispersibility and shortage of action time.
The polysiloxane group is modified through the norbornene structure, and the defoaming water reducing agent with hyperbranched structure is prepared by ring-opening metathesis polymerization method, which increases the working time of the low-viscosity defoaming agent and slows down through hydrolysis Release the defoamer to enhance adsorption and dispersion of cement particles.
It significantly improves the flowability and dispersion of concrete, reduces the gas content, enhances the resistance performance, and the prepared cable cover plate has smooth surface and excellent resistance performance, meeting the requirements of high-performance concrete.
Smart Images

Figure CN118834050B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to a self-compacting high-performance concrete cable cover plate. Background Art
[0002] Cable trench covers are one of the most commonly used auxiliary facilities in power systems. Their main function is to prevent foreign objects from falling into the trench and to protect cables, terminal boxes, etc. in the trench. Self-compacting concrete is a high-performance concrete with good fluidity. It can completely fill complex molds, ensure the consistent performance of all parts of the cover, and improve product quality stability; high density, forming a dense microstructure, improving anti-permeability and durability; usually has high strength, can make thinner and lighter covers for easy installation and maintenance.
[0003] However, the self-compacting concrete has too many cementitious material components and a high powder content, which leads to a large water demand, easy self-shrinkage and drying shrinkage, and increased cracking risk. Polycarboxylic acid water reducer has the advantages of high water reduction rate, adjustable molecular structure and green environmental protection. With the development of the concrete industry and the improvement of various performance requirements of concrete, polycarboxylic acid water reducer has been widely and rapidly applied. However, due to the characteristics of its own molecular structure, carboxylic acid water reducer has strong air entraining ability, which introduces bubbles of different sizes during the preparation of concrete, and the air content is too high, which seriously affects the strength, appearance and durability of concrete. Polydimethylsiloxane, as a common defoamer, has a defoaming ability that changes with its viscosity. When the viscosity is small, the defoaming ability is strong and easy to disperse, but it is easy to be adsorbed by cement particles, resulting in a short action time; as the viscosity increases, it can provide a longer defoaming effect, but the dispersibility gradually decreases, which is easy to affect the fluidity of cement. Hyperbranched polymers have good molecular plasticity, strong dispersibility and low intrinsic viscosity. At present, there is no report on the research and development of hyperbranched defoaming water reducers. Therefore, it is very necessary to develop a defoaming water-reducing agent with a hyperbranched structure for self-compacting concrete and its preparation. Summary of the invention
[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention adopts norbornene structure to modify polysiloxane groups and amino compounds, and obtains a defoaming water reducer with a hyperbranched structure by ring-opening metathesis polymerization. When the water reducer is added to alkaline concrete, the defoamer is slowly released through hydrolysis reaction, thereby increasing the action time of the low-viscosity defoamer. After the outer layer is hydrolyzed, the water reducer with a hyperbranched structure has good adsorption and dispersibility on cement particles, thereby reducing the water-cement ratio.
[0005] The technical solution of the present invention is as follows: a self-compacting high-performance concrete cable cover, which is composed of a self-compacting high-performance concrete and a steel frame, characterized in that the self-compacting high-performance concrete, in terms of mix ratio, includes 300-400 kg / m 3 Silica fume 100~120kg / m 3 、Fly ash 60~80kg / m 3 , Sand 700~850kg / m 3 , Crushed stone 850~950kg / m 3 , Steel fiber 120~160kg / m 3 , Defoaming water reducing agent 10~15kg / m 3 , Water 140~180kg / m 3 ; The defoaming water reducing agent is obtained by the following steps:
[0006] S1. Synthesis of polysiloxane monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add triethylamine, and then add polysiloxane to the reactor at room temperature. Heat to 100-120°C and react for 8-16 hours. Stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash with sodium hydroxide aqueous solution and hydrochloric acid aqueous solution three times each, collect the organic phase, and evaporate to obtain polysiloxane monomer;
[0007] S2. Synthesis of difunctional amino monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add triethylamine, then add diamino compound to the reactor at room temperature, heat to 80-120°C and react for 8-16 hours, stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash with aqueous hydrochloric acid solution and aqueous sodium hydroxide solution three times respectively, collect the organic phase, and evaporate to obtain a difunctional amino monomer;
[0008] S3. Synthesis of monofunctional amino monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add triethylamine, and then add a monoamino compound to the reactor at room temperature. Heat to 100-120° C. and react for 8-16 hours. Stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash three times with sodium hydroxide aqueous solution, collect the organic phase, and evaporate to obtain a monofunctional amino monomer;
[0009] S4. Synthesis of defoaming water reducer: Under nitrogen atmosphere, add 1 eq of the obtained difunctional amino monomer and 4-9 eq of monofunctional amino monomer and a catalyst dissolved in a solvent into a reactor to carry out ring-opening metathesis polymerization. After heating to 50-100°C for reaction for 0.5-1h, slowly add 2-5 eq of polysiloxane monomer and continue to react for 2-3h. The molar ratio of the added catalyst to the sum of the difunctional amino monomer and the monofunctional amino monomer is 1:(20-50). After the reaction is completed, add vinyl ethyl ether to quench the reaction, remove the solvent, and obtain a defoaming water reducer with a hyperbranched structure through recrystallization from acetone.
[0010] It should be noted that:
[0011] In the washing steps involved in the present invention, the volume ratio of the washing solvent to the washing liquid is 1:5.
[0012] The concentration of the sodium hydroxide aqueous solution and the hydrochloric acid aqueous solution used in steps S1 to S3 is 1 to 2 mol / L.
[0013] Preferably, the sand is Qingyuan river sand with a fineness modulus of 2.7 to 3.0; the steel fiber is a copper-plated steel fiber with a length of 12 to 14 mm and a diameter of 0.18 to 0.22 mm; preferably, the silica fume is semi-densified silica fume with a SiO2 content of 96%; and the gravel has a particle size of 5 to 8 mm.
[0014] The present invention uses a difunctional monomer and two different monofunctional monomers to copolymerize through ring-opening metathesis polymerization, and controls the ratio between the monomers and the ratio between the monomers and the catalyst to obtain defoaming water reducers with different molecular weights and different branching degrees. The monofunctional monomers are polysiloxane monomers and monofunctional amino monomers.
[0015] Preferably, the polysiloxane is hydroxyl-terminated polydimethylsiloxane, and the viscosity of the hydroxyl-terminated polydimethylsiloxane is 25-100 cSt.
[0016] Preferably, the monoamino compound is aminopolyethylene glycol monomethyl ether, and the molecular weight of the aminopolyethylene glycol monomethyl ether is 2000-5000.
[0017] Preferably, the diamino compound has one or more of the following molecular structures of Formula I and Formula II:
[0018]
[0019] In formula I, a=2-10; in formula II, b=43-110.
[0020] More preferably, the diamino compound is ethylenediamine, and further preferably is the hydrochloride of ethylenediamine in Formula 1.
[0021] Preferably, the catalyst is one or more of Grubbs first generation catalyst, Grubbs second generation catalyst, and Grubbs third generation catalyst.
[0022] More preferably, the catalyst is a Grubbs second generation catalyst.
[0023] Preferably, the solvent in step S4 is one or more of dichloromethane, chloroform, tetrahydrofuran and toluene.
[0024] More preferably, the solvent in step S4 is toluene.
[0025] Preferably, in step S1, the molar ratio of nadic anhydride, polysiloxane and triethylamine is (1-1.5):1:(1.5-3); in step S2, the molar ratio of nadic anhydride, diamino compound and triethylamine is (2.5-3):1:(2.5-3); in step S3, the molar ratio of nadic anhydride, monoamino compound and triethylamine is (1-1.5):1:(1.5-3).
[0026] Preferably, the edge protection steel frame is welded from equilateral angle steels.
[0027] Preferably, the cross-sectional size of the equilateral angle steel is 20*20*3mm.
[0028] The present invention also protects a method for preparing the self-compacting high-performance concrete cable cover, comprising the following steps:
[0029] 1) After cleaning the mold surface with 0.6-0.8MPa compressed air, apply a water-based release agent to the mold. The thickness of the release agent is 0.1-0.2mm and the coverage is 20-40m 2 / L, leave it for 30-60 minutes after applying, and accurately place the edge protection steel frame at the bottom of the mold;
[0030] 2) Mix cement, silica fume, fly ash, sand and gravel according to the mix ratio, stir for 1 to 5 minutes, add water, stir for 2 to 5 minutes, add defoaming water reducer, continue stirring for 2 to 10 minutes, then slowly add steel fiber and continue stirring for 2 to 10 minutes, then discharge;
[0031] 3) Mix cement, silica fume, fly ash, sand and crushed stone according to the mix ratio, stir for 1 to 5 minutes, add water, stir for 2 to 5 minutes, then add defoaming water reducer, continue stirring for 2 to 10 minutes, and discharge;
[0032] 4) Layered pouring is adopted. The concrete obtained in step 3) is poured into the mold with a thickness of 4 to 5 mm. The remaining part is poured with the concrete obtained in step 2). After the concrete is allowed to flow naturally to fill the mold, the concrete is immediately smoothed. The surface needs to be slightly higher than the mold frame. A flat vibrator is used to vibrate for 5 to 10 seconds. After vibration, the surface is smoothed with a trowel so that the aggregate is not exposed and the surface is flat. After 48 hours of film curing, the concrete is demolded and normally cured for 26 days.
[0033] Beneficial Effects
[0034] The present invention adopts ring-opening metathesis polymerization to efficiently combine the water reducer and the defoamer to obtain a defoaming water reducer with a hyperbranched structure, which has the following beneficial effects compared with the prior art:
[0035] 1) The hyperbranched water reducer with a rigid ring structure as the main chain and a high molecular weight amino polyethylene glycol monomethyl ether as the side chain has greater steric hindrance and can more effectively disperse cement molecules in concrete.
[0036] 2) The hyperbranched polymer molecular structure contains imide, silicone, carboxylic acid and polyethylene glycol monomethyl ether groups. As the stirring time in the concrete increases, the silicone and imide structures are gradually hydrolyzed to obtain amide, silanol, polyethylene glycol monomethyl ether and carboxylate. Among them, silanol plays a defoaming role, polyethylene glycol monomethyl ether plays a steric hindrance role, and the carboxylate has an anchoring structure.
[0037] 3) During polymerization, the monomers are added in batches to obtain a hyperbranched structure, the outer layer of which is polysilicone and carboxylic acid groups, and the inner layer of which is polyethylene glycol monomethyl ether and carboxylic acid groups. This inner and outer layer structure causes the water reducer just added to the concrete to have a weak interaction force with the cement due to the steric hindrance of the outer layer of polysilicone, so that it can be evenly dispersed in the concrete. With the hydrolysis of the outer layer of silicone, the steric hindrance becomes smaller and smaller, and the increase of carboxylate groups, the interaction force between the water reducer and the cement gradually increases, playing the role of reducing water and dispersing cement. At a later stage, the imide groups in the internal structure also begin to hydrolyze, and more carboxylate structures are anchored to the cement, which enhances the interaction force between cement molecules, increases the stability of the overall structure, and reduces the internal pores;
[0038] 4) Compared with emulsified defoamers, the obtained defoaming water reducer can be dissolved in water, does not need emulsification, has higher stability and better dispersibility.
[0039] The self-compacting high-performance concrete obtained by the defoaming water-reducing agent has good fluidity and low air content. The cable cover prepared by the concrete has the advantages of smooth surface and excellent resistance performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The present invention provides a synthetic route and dispersion mechanism of the defoaming and water reducing agent;
[0041] Figure 2 is the H-NMR spectrum of the polysiloxane monomer 2 of the present invention;
[0042] Figure 3 It is the nuclear magnetic hydrogen spectrum of the defoaming water reducing agent 7 of the present invention. DETAILED DESCRIPTION
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0045] The raw materials used in the embodiments and comparative examples are described as follows:
[0046] Nadic anhydride: Shanghai MacLean, product number N814504;
[0047] Hydroxyl-terminated polydimethylsiloxane 1: viscosity 25 cSt, Shanghai MacLean, product number 768080;
[0048] Hydroxyl-terminated polydimethylsiloxane 2: viscosity 40 cSt, Shanghai MacLean, product number P856624;
[0049] Hydroxyl-terminated polydimethylsiloxane 3: viscosity 65 cSt, Shanghai MacLean, product number 768077;
[0050] Hydroxyl-terminated polydimethylsiloxane 4: viscosity 100 cSt, Jinan Longcheng Silicone;
[0051] Hydroxyl-terminated polydimethylsiloxane 5: viscosity 200 cSt, Jinan Longcheng Silicone;
[0052] Polyethylene glycol monomethyl ether 1: average molecular weight 2000, Guangzhou Bairui Pharmaceutical;
[0053] Polyethylene glycol monomethyl ether 2: average molecular weight 5000, Guangzhou Bairui Pharmaceutical;
[0054] Polyethylene glycol monomethyl ether 3: average molecular weight 1000, Shanghai McLean;
[0055] Polyethylene glycol monomethyl ether 4: average molecular weight 8000, Guangzhou Bairui Pharmaceutical;
[0056] Ethylenediamine hydrochloride: Hubei Qifei Pharmaceutical Chemicals, product number QF4160;
[0057] p-Toluenesulfonyl chloride: Anaiji Chemical, product number T35955;
[0058] Grubbs second-generation catalyst: Anaiji Chemical, product number G789000;
[0059] Cement: Portland cement, PII 52.5R, produced by Zhujiang Cement Plant;
[0060] Silica fume: semi-densified silica fume, SiO2 content 96%, purchased from Sichuan Ewende, 960U;
[0061] Fly ash: Class II fly ash, Wuhan Lianhekang Biotechnology Co., Ltd.;
[0062] Sand: Qingyuan river sand, fineness modulus 2.7-3.0;
[0063] Crushed stone: purchased from Chaolian Dongxing Sand Field in Pengjiang District, Jiangmen City, with a particle size of 5-8 mm;
[0064] Steel fiber: copper-plated steel fiber, diameter 0.20mm, length 13mm, Anping County Lianzhu Steel Fiber;
[0065] Equilateral angle steel: cross-sectional dimensions are 20*20*3mm, from Foshan Gangsu Steel;
[0066] Water-based release agent: Product No. YLD-T-01, Shandong Yonglida New Material Technology;
[0067] Commercially available water reducer: standard polycarboxylate water reducer, Guangdong Wengjiang Chemical Reagent, PA96208;
[0068] Aminopolyethylene glycol monomethyl ether 1: Aminopolyethylene glycol monomethyl ether, average molecular weight 2000, homemade, preparation method is as follows: in a nitrogen atmosphere, add 1eq of polyethylene glycol monomethyl ether 1 with average molecular weight 2000, 3eq of p-toluenesulfonyl chloride, 3eq of triethylamine to a reactor, use dichloromethane as solvent, stir at 50°C for 10h, wait for the reaction to end. First wash three times with 1mol / L hydrochloric acid solution, then wash three times with 1mol / L sodium hydroxide aqueous solution, collect the organic phase and evaporate.
[0069] The obtained solid was dissolved in ammonia water, stirred at room temperature for three days, and then a 2 mol / L sodium hydroxide aqueous solution was added and stirred for 2 h. The mixture was extracted with dichloromethane three times, and the organic phase was collected, evaporated, and recrystallized from diethyl ether to obtain aminopolyethylene glycol monomethyl ether 1.
[0070] Aminopolyethylene glycol monomethyl ether 2: The preparation method is compared with aminopolyethylene glycol monomethyl ether 1, except that polyethylene glycol monomethyl ether 1 is replaced by polyethylene glycol monomethyl ether 2, and the average molecular weight is 5000.
[0071] Aminopolyethylene glycol monomethyl ether 3: The preparation method is compared with aminopolyethylene glycol monomethyl ether 1, except that polyethylene glycol monomethyl ether 1 is replaced by polyethylene glycol monomethyl ether 3, and the average molecular weight is 1000.
[0072] Aminopolyethylene glycol monomethyl ether 4: The preparation method is compared with aminopolyethylene glycol monomethyl ether 1, except that polyethylene glycol monomethyl ether 1 is replaced by polyethylene glycol monomethyl ether 4, and the average molecular weight is 8000.
[0073] (1) Relative molecular weight: gel permeation chromatography-differential detector (Waters, USA);
[0074] (2) Molecular weight distribution: Gel permeation chromatography-differential detector (Waters, USA). The higher the degree of branching, the wider the molecular weight distribution is generally.
[0075] (3) NMR spectrum: 400 MHz NMR spectrometer (Bruker, Germany);
[0076] (4) Surface tension: measured in accordance with GB / T 8077-2023 Test method for homogeneity of concrete admixtures;
[0077] (5) Water reduction rate: measured in accordance with GB / T 8077-2023 Test method for homogeneity of concrete admixtures;
[0078] (6) Slump expansion: JGJ / T 283-2012 Technical Specification for Application of Self-compacting Concrete;
[0079] (7) Compressive strength: The specimen size is 150 mm × 150 mm × 150 mm, and the test is carried out in accordance with the relevant provisions of GB / T50081-2019;
[0080] (8) Air content: GB / T50080-2016 "Standard for test methods for properties of ordinary concrete mixtures";
[0081] (9) Cracking load: The cover size is 1400 mm × 300 mm × 60 mm, and the detection method is the "Cable Manhole Cover Marking Technical Book" of China Southern Power Grid;
[0082] (10) Destruction load: The cover size is 1400 mm × 300 mm × 60 mm, and the detection method is the "Cable Manhole Cover Marking Technical Book" of China Southern Power Grid.
[0083] The polysiloxane monomer in the present invention is obtained by the following steps:
[0084] Polysiloxane Monomer 1
[0085] Under a nitrogen atmosphere, 1.5 mol of nadic anhydride was added to a reactor and dissolved in toluene. After adding 2 mol of triethylamine, 3 mol of hydroxy-terminated polydimethylsiloxane 1 was added to the reactor at room temperature. The temperature was raised to 100°C and the reaction was carried out for 10 hours. The reaction was stopped and the toluene was removed by evaporation. The obtained product was dissolved in dichloromethane and washed three times with an aqueous sodium hydroxide solution and an aqueous hydrochloric acid solution. The organic phase was collected and evaporated to obtain a polysiloxane monomer 1.
[0086] Polysiloxane monomer 2~5
[0087] The preparation method is compared with amino polyethylene glycol monomethyl ether 1, and the difference lies in that hydroxyl-terminated polydimethylsiloxane 1 is replaced by hydroxyl-terminated polydimethylsiloxane 2-5.
[0088] The difunctional amino monomer of the present invention is obtained by the following steps:
[0089] Under a nitrogen atmosphere, 3 mol of nadic anhydride was added to the reactor and dissolved in toluene. After adding 3 mol of triethylamine, 1 mol of ethylenediamine was added to the reactor at room temperature. The temperature was raised to 80°C and the reaction was reacted for 10 hours. The reaction was stopped and the toluene was evaporated to remove the toluene. The obtained product was dissolved in dichloromethane and washed three times with aqueous hydrochloric acid solution and aqueous sodium hydroxide solution in sequence. The organic phase was collected and evaporated to obtain a difunctional amino monomer.
[0090] The monofunctional amino monomer in the present invention is obtained by the following steps:
[0091] Monofunctional amino monomer 1
[0092] Under a nitrogen atmosphere, 1.5 mol of nadic anhydride was added to a reactor and dissolved in toluene. After adding 2 mol of triethylamine, 1 mol of aminopolyethylene glycol monomethyl ether 1 was added to the reactor at room temperature. The temperature was raised to 110°C and the reaction was reacted for 8 hours. The reaction was stopped and the toluene was evaporated to remove the toluene. The obtained product was dissolved in dichloromethane and washed three times with aqueous sodium hydroxide solution. The organic phase was collected and evaporated to obtain a monofunctional amino monomer.
[0093] Monofunctional amino monomer 2~4
[0094] The preparation method is compared with the monofunctional amino monomer 1, and the difference is that the amino polyethylene glycol monomethyl ether 1 is replaced by amino polyethylene glycol monomethyl ethers 2-4.
[0095] The defoaming water reducing agent of the present invention is prepared by the following steps, and its relative molecular weight, molecular weight distribution, surface tension and water reduction rate are measured as shown in Table 1:
[0096] Defoaming water reducing agent 1
[0097] Under a nitrogen atmosphere, 1 mol of the obtained difunctional amino monomer and 4 mol of the monofunctional amino monomer 1 and 0.1 mol of the Grubbs second-generation catalyst were added to a reactor and dissolved in a solvent to carry out ring-opening metathesis polymerization. After the temperature was raised to 100° C. and the reaction was continued for 1 hour, 2 mol of the polysiloxane monomer 1 was slowly added and the reaction was continued for 2 to 3 hours. Vinyl ethyl ether was added to quench the reaction, the solvent was removed, and a hyperbranched defoaming water reducer was obtained by recrystallization through acetone.
[0098] Defoaming water reducing agent 2
[0099] Under a nitrogen atmosphere, 1 mol of the obtained difunctional amino monomer and 9 mol of the monofunctional amino monomer 1 and 0.5 mol of the Grubbs second-generation catalyst were added to a reactor and dissolved in a solvent to carry out ring-opening metathesis polymerization. After the temperature was raised to 100° C. and the reaction was continued for 1 hour, 5 mol of the polysiloxane monomer 1 was slowly added and the reaction was continued for 2 to 3 hours. Vinyl ethyl ether was added to quench the reaction, the solvent was removed, and a hyperbranched defoaming water reducer was obtained by recrystallization through acetone.
[0100] Defoaming water reducing agent 3
[0101] Under a nitrogen atmosphere, 1 mol of the obtained difunctional amino monomer and 7 mol of the monofunctional amino monomer 1 and 0.2 mol of the Grubbs second-generation catalyst were added to a reactor and dissolved in a solvent to carry out ring-opening metathesis polymerization. After the temperature was raised to 100° C. and the reaction was continued for 1 hour, 3 mol of the polysiloxane monomer 1 was slowly added and the reaction was continued for 2 to 3 hours. Vinyl ethyl ether was added to quench the reaction, the solvent was removed, and a hyperbranched defoaming water reducer was obtained by recrystallization through acetone.
[0102] Defoaming water reducing agent 4
[0103] The preparation method is compared with the defoaming water reducer 3, except that the monofunctional amino monomer 1 is replaced by the monofunctional amino monomer 2.
[0104] Defoaming water reducing agent 5
[0105] The preparation method is compared with the defoaming water reducer 3, except that the monofunctional amino monomer 1 is replaced by the monofunctional amino monomer 3.
[0106] Defoaming water reducing agent 6
[0107] The preparation method is compared with the defoaming water reducer 3, except that the monofunctional amino monomer 1 is replaced by the monofunctional amino monomer 4.
[0108] Defoaming water reducing agent 7
[0109] The preparation method is compared with the defoaming water reducer 3, the difference being that the polysiloxane monomer 1 is replaced by the polysiloxane monomer 2.
[0110] Defoaming water reducing agent 8
[0111] The preparation method is compared with the defoaming water reducer 3, except that the polysiloxane monomer 1 is replaced by the polysiloxane monomer 3.
[0112] Defoaming water reducing agent 9
[0113] The preparation method is compared with the defoaming water reducer 3, except that the polysiloxane monomer 1 is replaced by the polysiloxane monomer 4.
[0114] Defoaming water reducing agent 10
[0115] The preparation method is compared with the defoaming water reducing agent 3, except that the polysiloxane monomer 1 is replaced by the polysiloxane monomer 5.
[0116] Defoaming water reducing agent 11
[0117] The preparation method is compared with the defoaming water reducer 3, except that 0.2 mol of Grubbs second-generation catalyst is replaced by 0.1 mol of Grubbs second-generation catalyst.
[0118] Defoaming water reducing agent 12
[0119] The preparation method is compared with the defoaming water reducer 3, except that 0.2 mol of Grubbs second-generation catalyst is replaced by 1 mol of Grubbs second-generation catalyst.
[0120] Defoaming water reducing agent 13
[0121] The preparation method is compared with the defoaming water reducer 3, except that 7 mol of the monofunctional amino monomer 1 is replaced by 2 mol of the monofunctional amino monomer 1.
[0122] Defoaming water reducing agent 14
[0123] The preparation method is compared with the defoaming water reducer 3, except that 1 mol of the difunctional amino monomer 1 is replaced by no addition, and a linear copolymer is obtained.
[0124] Depend on Figure 2 The nuclear magnetic proton spectrum showed that the polysiloxane monomer 2 was successfully synthesized; Figure 3 The H-NMR spectrum showed the change of double bond chemical shift, indicating that the polymerization was successfully carried out.
[0125] Table 1 Defoaming water reducing agent properties
[0126]
[0127] A self-compacting concrete cable cover, the preparation method comprising the following steps:
[0128] 1) After cleaning the mold surface with 0.6Mpa compressed air, apply a water-based release agent to the mold. The thickness of the release agent is 0.2mm and the coverage is 30m 2 / L, leave it for 50 minutes after applying, and accurately place the edge protection steel frame at the bottom of the mold;
[0129] 2) Mix cement, silica fume, fly ash, sand and gravel according to the mix ratio, stir for 2 minutes, add water, stir for 2 minutes, add defoaming water reducer, continue stirring for 6 minutes, then slowly add steel fiber and continue stirring for 7 minutes, then discharge;
[0130] 3) Mix cement, silica fume, fly ash, sand and gravel according to the mix ratio, stir for 2 minutes, add water, stir for 2 minutes, add defoaming water reducer, continue stirring for 8 minutes, and discharge;
[0131] 4) Use layered pouring to pour the concrete obtained in step 3) into the mold. The thickness of the first layer is 5 mm. The remaining part is poured with the concrete obtained in step 2). After the concrete flows naturally to fill the mold, the concrete is immediately smoothed. The surface needs to be slightly higher than the mold frame. Use a flat vibrator to vibrate for 8 seconds. After vibration, use a trowel to smooth the surface so that the aggregate is not exposed and the surface is flat. After 48 hours of film curing, demolding and ordinary curing for 26 days.
[0132] Table 2 Self-compacting concrete cable cover formulation (Examples 1 to 12, in terms of mix ratio kg / m 3 )
[0133]
[0134] Comparative Example 1
[0135] The preparation method is compared with Example 3, except that the defoaming water reducer is replaced by a mixture 1 obtained by blending a commercially available water reducer and hydroxyl-terminated polydimethylsiloxane 1 in a mass ratio of 5:1.
[0136] Comparative Examples 2 to 6
[0137] The preparation method is consistent with that of Examples 1 to 12.
[0138] Table 3 Self-compacting concrete cable cover formulation (Comparative Examples 1 to 6, in terms of mix ratio kg / m 3 )
[0139]
[0140] Table 4 Performance test results of embodiments and comparative examples
[0141]
[0142]
[0143] From the data of the examples and comparative examples, it can be seen that the slump expansion of the self-compacting concrete prepared by appropriately adding the defoaming water-reducing agent prepared within the preferred range of the present invention is greater than 660mm, reaching the concrete self-compacting grade SF2, and is suitable for general ordinary reinforced concrete structures; the compressive strength is greater than 60Mpa, which meets the national high-performance concrete standard. The prepared 60mm cable cover has an air content of less than 2.0%, a smooth surface and uniform color; the cracking load is greater than 16000N, and the failure load is greater than 32000N, which meets the performance requirements of pedestrian cable manhole covers, and the cover thickness is 20mm thinner than the standard cover.
[0144] From the data in Table 1, it can be seen that as the molecular weight of the monofunctional amino monomer increases during polymerization, the water reduction rate of the defoaming water reducer increases, and the surface tension has little effect; as the viscosity of the polysiloxane monomer increases, its molecular weight increases, the water reduction rate decreases, and the surface tension first decreases and then increases; the higher the degree of branching, the higher the water reduction rate and the smaller the surface tension. When the proportion of the bifunctional monomer is too high, the resulting water reducer will become a cross-linked polymer and cannot be used in concrete.
[0145] It can be seen from the data in Table 4 that the better the performance of the concrete, the higher the performance of the prepared cable cover plate; it can be seen from the data of Examples 3-5 and Comparative Example 6 that the higher the degree of branching of the defoaming water-reducing agent used, the higher the mechanical properties of the concrete and the lower the air content; it can be seen from the data of Examples 5 to 8 that the higher the molecular weight inside the defoaming water-reducing agent molecule, the greater the compressive strength of the prepared concrete, the greater the slump expansion, but the air content increases; it can be seen from the data of Examples 5, 9 to 12 that the greater the molecular weight of the defoaming type outside, the air content of the prepared concrete first increases and then decreases, and the compressive strength and slump expansion gradually decrease; it can be seen from the data of Comparative Example 1 that the performance of the prepared concrete is poor when a mixture of a commercially available water-reducing agent and a hydroxyl-terminated polydimethylsiloxane 1 is added; it can be seen from the data of Comparative Examples 2 to 3 that an appropriate amount of the defoaming water-reducing agent of the present invention can improve the performance of the concrete; it can be seen from the data of Comparative Examples 4 to 5 that the performance of the concrete can be improved within a certain range of the molecular weight of the defoaming water-reducing agent.
[0146] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A self-compacting high-performance concrete cable cover, characterized in that: It is composed of self-compacting high-performance concrete and edge protection steel frame. The self-compacting high-performance concrete includes 300-400 kg / m of cement according to the mix ratio. 3 Silica fume 100~120kg / m 3 、Fly ash 60~80kg / m 3 , Sand 700~850kg / m 3 , Crushed stone 850~950kg / m 3 , Steel fiber 120~160kg / m 3 , Defoaming water reducing agent 10~15kg / m 3 , Water 140~180kg / m 3 ; The defoaming water reducing agent is obtained by the following steps: S1. Synthesis of polysiloxane monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add triethylamine, and then add polysiloxane to the reactor at room temperature. Heat to 100-120°C and react for 8-16 hours. Stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash with sodium hydroxide aqueous solution and hydrochloric acid aqueous solution three times each, collect the organic phase, and evaporate to obtain a polysiloxane monomer; S2. Synthesis of difunctional amino monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add triethylamine, then add diamino compound to the reactor at room temperature, heat to 80-120°C and react for 8-16 hours, stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash with aqueous hydrochloric acid solution and aqueous sodium hydroxide solution three times respectively, collect the organic phase, and evaporate to obtain a difunctional amino monomer; S3. Synthesis of monofunctional amino monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add triethylamine, and then add a monoamino compound to the reactor at room temperature. Heat to 100-120° C. and react for 8-16 hours. Stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash three times with sodium hydroxide aqueous solution, collect the organic phase, and evaporate to obtain a monofunctional amino monomer; S4. Synthesis of defoaming water reducing agent: Under nitrogen atmosphere, add 1 eq of the obtained difunctional amino monomer and 4-9 eq of monofunctional amino monomer and a catalyst dissolved in a solvent into a reactor to carry out ring-opening metathesis polymerization. After heating to 50-100°C for reaction for 0.5-1h, slowly add 2-5 eq of polysiloxane monomer and continue to react for 2-3h. The molar ratio of the added catalyst to the sum of the difunctional amino monomer and the monofunctional amino monomer is 1:(20-50). After the reaction is completed, vinyl ethyl ether is added to quench the reaction, the solvent is removed, and a defoaming water reducing agent with a hyperbranched structure is obtained by recrystallization from acetone. The polysiloxane is a hydroxyl-terminated polydimethylsiloxane having a viscosity of 25-100 cSt.
2. The concrete cable cover plate according to claim 1, characterized in that: The diamino compound has one or more of the following molecular structures of Formula I and Formula II: In formula I, a=2-10; in formula II, b=43-110.
3. The concrete cable cover plate according to claim 1, characterized in that: The monoamino compound is aminopolyethylene glycol monomethyl ether, and the molecular weight of the aminopolyethylene glycol monomethyl ether is 2000-5000.
4. The concrete cable cover plate according to claim 1, characterized in that: The catalyst is one or more of a Grubbs first generation catalyst, a Grubbs second generation catalyst, and a Grubbs third generation catalyst.
5. The concrete cable cover plate according to claim 1, characterized in that: The solvent in step S4 is one or more of dichloromethane, chloroform, tetrahydrofuran and toluene.
6. The concrete cable cover plate according to claim 1, characterized in that: In step S1, the molar ratio of nadic anhydride, polysiloxane and triethylamine is (1-1.5):1:(1.5-3); in step S2, the molar ratio of nadic anhydride, diamino compound and triethylamine is (2.5-3):1:(2.5-3); in step S3, the molar ratio of nadic anhydride, monoamino compound and triethylamine is (1-1.5):1:(1.5-3).
7. The concrete cable cover plate according to claim 1, characterized in that: The edge protection steel frame is welded by angle steel.
8. The method for preparing the self-compacting concrete cable cover plate according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) After cleaning the mold surface with 0.6-0.8MPa compressed air, apply a water-based release agent to the mold. The thickness of the release agent is 0.1-0.2mm and the coverage is 20-40m 2 / L, leave it for 30-60 minutes after applying, and accurately place the edge protection steel frame at the bottom of the mold; 2) Mix cement, silica fume, fly ash, sand and gravel according to the mix ratio, stir for 1 to 5 minutes, add water, stir for 2 to 5 minutes, add defoaming water reducer, continue stirring for 2 to 10 minutes, then slowly add steel fiber and continue stirring for 2 to 10 minutes, then discharge; 3) Mix cement, silica fume, fly ash, sand and gravel according to the mix ratio, stir for 1 to 5 minutes, add water, stir for 2 to 5 minutes, then add defoaming water reducer, continue stirring for 2 to 10 minutes and discharge; 4) Layered pouring is adopted. The concrete obtained in step 3) is poured into the mold with a thickness of 4 to 5 mm. The remaining part is poured with the concrete obtained in step 2). After the concrete is allowed to flow naturally to fill the mold, the concrete is immediately smoothed. The surface needs to be slightly higher than the mold frame. A flat vibrator is used to vibrate for 5 to 10 seconds. After vibration, the surface is smoothed with a trowel so that the aggregate is not exposed and the surface is flat. After 48 hours of film curing, the concrete is demolded and normally cured for 26 days.
Citation Information
Patent Citations
Bridge self-compaction anti-crack bare concrete prepared by utilizing high fine powder content machine-made sand
CN107265966A
Ultrahigh-strength self-compaction micro-expansion steel pipe-encased concrete and preparation method thereof
CN109678433A
Concrete with high fluidity
JP2018184330A
Polymer for Ultra-High Strength Concrete Admixture and Method for Preparing the Same
US20100324175A1
Application of high toughness, low viscosity nano-molecular resin for reinforcing pothole patching materials in asphalt and concrete base pavement
US20110293954A1
